Volume shrinkage and abrasive wear properties of crosslinked Poly(ester-urethane-acrylate)/MMA copolymer: Effect of chain length. Issue 1 (2nd January 2018) - Maurya, Shyam Dev; Kurmvanshi, S. K.; Mohanty, S.; Nayak, Sanjay K.
ABSTRACT: The current study deals with the preparation of novel crosslink transparent poly(ester-urethane-acrylate)/methyl methacrylate (TPEUMA) copolymers and the effect of hydroxyl terminated aromatic polyester (PEs) was also investigated. The properties of TPEUMA were investigated in terms of double bond concentration, polymerization shrinkage, abrasive wear analysis and chemical resistance. The volume shrinkage decreased due to the significant reduction in the concentration of double bonds. The first two effects reflect in lowering the abrasive wear resistance properties at room temperature, while the larger chain length between crosslink decreases the hardness. Decrease in polymerization shrinkage shows more condensed microstructure which was revealed by the abrasive wear rate of TPEUMAs due to hydrogen bonding near to crosslink point. Increase in the chain length of PEs, decreases the glass transition temperature of TPEUMA copolymer which results in loose microstructure. Worn surface were studied using scanning electron microscope to give insight on the wear mechanism of TPEUMA crosslink. It can be suggested from the present study that this copolymer can be used for a broad range of optical applications.